2014
DOI: 10.1001/jamainternmed.2014.2488
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Patient-Centered Medical Home in the Veterans Health Administration

Abstract: IMPORTANCE In 2010, the Veterans Health Administration (VHA) began implementing the patient-centered medical home (PCMH) model. The Patient Aligned Care Team (PACT) initiative aims to improve health outcomes through team-based care, improved access, and care management. To track progress and evaluate outcomes at all VHA primary care clinics, we developed and validated a method to assess PCMH implementation.OBJECTIVES To create an index that measures the extent of PCMH implementation, describe variation in imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
127
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(140 citation statements)
references
References 34 publications
2
127
1
Order By: Relevance
“…1). Teamlets in Practice 1 (when fully staffed) conformed to the teamlet structure described in national PACT guidance, 11 where a panel of 1,200 patients was cared for by a PCP (or multiple part-time PCPs), a consistent RN care manager, LPN, and clerk. In contrast, in Practices 2 and 3, one or two clerks were assigned to registration desks in the front office, but the majority of clerks were centralized in appointment phone rooms and other non-patient care settings with little in-person interaction with Veterans.…”
Section: Interview Resultsmentioning
confidence: 99%
“…1). Teamlets in Practice 1 (when fully staffed) conformed to the teamlet structure described in national PACT guidance, 11 where a panel of 1,200 patients was cared for by a PCP (or multiple part-time PCPs), a consistent RN care manager, LPN, and clerk. In contrast, in Practices 2 and 3, one or two clerks were assigned to registration desks in the front office, but the majority of clerks were centralized in appointment phone rooms and other non-patient care settings with little in-person interaction with Veterans.…”
Section: Interview Resultsmentioning
confidence: 99%
“…VHA has been at the forefront of primary care redesign efforts that could improve homeless persons’ experiences with care (Nelson et al, 2014; O’Toole et al, 2011; Rosland et al, 2013). In 2010, VHA began reorganizing primary care providers and staff into Patient-Aligned Care Teams (PACTs) in an effort to deliver efficient, well-coordinated, comprehensive, patient-centered care.…”
mentioning
confidence: 99%
“…However, for remote electronic communication to be successful, face-to-face contact was also needed to build the relationships required. 100 Causal link 3:8 -multidisciplinary teams produce better demand management systems Three case studies in the UK 76 and the USA 66,102 provided evidence that MDTs could strengthen demand management systems and redistribute workload pressures across the care system. A multiple case study of five NHS vertical integration projects for paediatric/young persons' services 76 found that MDT working produced better gate-keeping and need-and/or risk-stratification.…”
Section: Causal Link 3:5 -Multidisciplinary Team Supports Voluntary Imentioning
confidence: 99%
“…GPs with access to advice and guidance from a consultant developed specialist expertise and could manage more complex cases without referring to secondary care, thus easing the workload there. 76 A study of the American Veterans Health Administration (VHA) 102 found that nurse visits in primary care were associated with a decreased risk of all-cause hospitalisation for veterans > 65 years of age. The Briot et al 66 case study of MHI in Utah 66 found evidence that MDT working redistributed workloads.…”
Section: Causal Link 3:5 -Multidisciplinary Team Supports Voluntary Imentioning
confidence: 99%